Developing Integrated Multimedia Communication for Deaf Students in Higher Education - Ratriyana, Ina Nur; Nuswantoro, Ranggabumi (PLD UIN Sunan Kalijaga, 2022)
Having communication with Deaf students is a challenge for some lecturers. Multimedia provides a potential solution for this situation; however, few people know how to develop it ideally. This study uses primary and secondary data to create a strategic model for multimedia-based learning for Deaf students through focus group discussion with the expert, lecturers, parents, and practitioners. At the same time, however, this model recognises that multimedia communication is not sufficient in and of itself for full engagement with them. This article, thus, proposes implementing several activities within universities based on four stages: identify the level of hard hearing, choose the learning style, design multimedia learning, and create engagement. By developing these strategies, Deaf students in higher education can have a comfortable and effective place to learn to minimize the communication barriers between Deaf student and others. Melakukan komunikasi dengan mahasiswa Tuli merupakan sebuah tantangan bagi para pengajar di pendidikan tinggi. Multimedia merupakan sebuah potensi sebagai solusi dalam situasi ini, hanya saja tidak semua orang memahami dengan baik cara implementasinya secara ideal. Penelitian ini menggunakan data primer dan sekunder untuk menciptakan model strategi berdasarkan pembelajaran berbasis multimedia untuk mahasiswa Tuli melalui diskusi kelompok dengan pihak yang berpengalaman, dosen, orang tua, dan juga praktisi di bidang ini. Pada saat bersamaan, model ini juga melihat bahwa komunikasi multimedia tidak cukup untuk membangun hubungan kedekatan dengan mahasiswa Tuli. Melalui artikel ini, peneliti mengajukan empat tahap pelaksanaan aktivitas di pendidikan tinggi yakni: identifikasi level Tuli, pemilihan gaya mengajar, desain multimedia, dan pembentukan hubungan. Melalui strategi ini, mahasiswa Tuli merasakan pendidikan tinggi dengan lebih nyaman dan efektif yang mampu mengurangi hambatan komunikasi antara mereka dengan yang lain.